The role of epithelial cells in COPD - Lababidi, R (2021)
Chronic Obstructive Pulmonary Disease (COPD) is a complex disease of the airways that results in the decline of lung function with patients having emphysema or chronic bronchitis pathologies and is responsible for 7% of global deaths per year. Smoking is the largest risk factor for causing COPD and COPD patients can experience exacerbations which is defined as worsening of the symptoms which often leads to hospitalizations. The strongest risk factors for exacerbations are bacterial or viral infections. Non-typeable haemophilus Influenzae (NTHi) and Rhinovirus (RV) in particular are associated with up to half of COPD exacerbations. The epithelium is the first line of defense against pathogens and responsible for keeping the microbiome in check. COPD patients have been shown to have a dysfunctional epithelium.